Association between aortic arch angulation and bird-beak configuration after thoracic aortic stent graft repair of type B aortic dissection. (7th October 2020) - Cao, Long; Ge, Yangyang; He, Yuan; Wang, Xinhao; Rong, Dan; Lu, Weihang; Liu, Xiaoping; Guo, Wei
Abstract: OBJECTIVES: The goal of this study was to investigate factors favouring the bird-beak configuration after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection. METHODS: We retrospectively analysed 76 patients with type B aortic dissection who underwent landing zone 1 and 2 TEVAR from December 2015 to January 2018. Preoperative aortic arch geometry (aortic arch length, maximal diameter and angulation), stent graft details and operative details were evaluated. A bird-beak configuration was defined as a ≥5-mm gap between the proximal end of the stent and the aortic wall of the lesser curvature. RESULTS: Patients were stratified into those with ( n = 46) and without ( n = 30) a bird-beak configuration. The baseline demographics, dissection chronicity, clinical features and implanted devices were largely similar between the 2 groups. No significant difference was observed in the arch length or maximal arch diameter. However, the mean aortic arch angulation was greater in patients with than without a bird-beak configuration (61.4° vs 51.3°; P < 0.001). No influence of either the stent graft brand or the proximal stent graft type was observed. The multivariable analysis showed that the aortic arch angulation was an independent risk factor for a bird-beak configuration (odds ratio 1.15, 95% confidence interval 1.07–1.24; P < 0.001). A cut-off angle of 59.15° was predictive of a bird-beak configuration (sensitivity 59%; specificity 77%). CONCLUSIONS: The preoperative aortic arch angulation was an independent predictor of a postoperative bird-beak configuration in patients with type B aortic dissection who underwent TEVAR that involved the aortic arch. An angle of >59.15° may imply a relatively hostile anatomy with a higher risk of a bird-beak configuration. Abstract : Thoracic endovascular aortic repair (TEVAR) has been established as an important and preferred treatment modality for type B aortic dissection (TBAD) [1].